2020
DOI: 10.1002/jmv.26654
|View full text |Cite
|
Sign up to set email alerts
|

Defining IL‐6 levels in healthy individuals: A meta‐analysis

Abstract: Background Interleukin‐6 (IL‐6) is produced by and impacts different cell types in human. IL‐6 is associated with different diseases and viral infections, including COVID‐19. To our knowledge, no normal values were reported for IL‐6 in the blood of healthy individuals. We have reviewed and performed a meta‐analysis on a total of 140 studies, including 12,421 values for IL‐6 in the blood of healthy adult donors. Among these studies, 83 did not report a mean value and the standard deviation. Therefore, for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 65 publications
5
68
0
1
Order By: Relevance
“…A meta-analysis study included 140 different research found that the average concentration of IL-6 in the majority of healthy people ranged between 4.631 and 5.740 pg/ml (ng/l) 29 . These variation might be attributed to differences in the weight of these people and their muscle mass and contractility status 29 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis study included 140 different research found that the average concentration of IL-6 in the majority of healthy people ranged between 4.631 and 5.740 pg/ml (ng/l) 29 . These variation might be attributed to differences in the weight of these people and their muscle mass and contractility status 29 .…”
Section: Discussionmentioning
confidence: 99%
“…anticytokine strategies). It is, however, worth considering that, when employing IL-6 levels to make clinical decisions, these should be interpreted with caution as they might be influenced by multiple confounding factors, such as age, comorbidities, treatments, and genetic polymorphisms [123].…”
Section: Il-6 As a Prognostic Marker In Covid-19mentioning
confidence: 99%
“…Therefore, plasma was used to measure these interleukin levels. 20 The patients gave 3 mL of peripheral venous blood in the early morning on an empty stomach. It was then centrifuged at room temperature (4000 rpm for 8 min), and the upper serum was stored in a refrigerator at −80°C.…”
Section: Methodsmentioning
confidence: 99%